The Malaysian women's experience of care and management of postnatal depression - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret; Yousuf, Abdilahi (Bentham Science Publishers, 2021)
Objectives: Early detection and intervention for Maternal Postnatal Depression (PND) are imperative to prevent devastating consequences for mothers, babies, and families. However, there are no guidelines that explicitly focus on the management of PND in Malaysia. Consequently, it is unclear whether women with PND are receiving proper care and treatment. Therefore, this study aimed to explore Malaysian Women's experience in managing PND symptoms. Methods: A qualitative study was conducted among 33 women attending Maternal and Child Health (MCH) clinics in Kuala Lumpur. Data were obtained through a face-to-face semi-structured interview and analysed using framework analysis. Results: The women considered PND as a personal and temporary issue. Therefore, professional care was deemed unnecessary for them. Additionally, all Malay women considered religious approach as their primary coping strategy for PND. However, this was not the case for most Indian and Chinese women. Conclusion: The findings of this study indicated that women did not acknowledge the roles of Healthcare Practitioners (HCPs) in alleviating their emotional distress. Also, they perceived PND as a personal problem and less serious emotional condition. It is due to this perception that the women adopted self-help care as their primary coping strategy for PND. However, the coping strategy varied between different cultures. These findings underscore the importance of HCPs’ proactive action to detect and alleviate PND symptoms as their attitude towards PND may influence Women's helpseeking behaviour.